2019
DOI: 10.1002/jssc.201900089
|View full text |Cite
|
Sign up to set email alerts
|

Fabric phase sorptive extraction/GC‐MS method for rapid determination of broad polarity spectrum multi‐class emerging pollutants in various aqueous samples

Abstract: A rapid extraction and cleanup method using selective fabric phase sorptive extraction combined with gas chromatography and mass spectrometry has been developed and validated for the determination of broad polarity spectrum emerging pollutants, ethyl paraben, butyl paraben, diethyl phthalate, dibutyl phthalate, lidocaine, prilocaine, triclosan, and bisphenol A in various aqueous samples. Some important parameters of fabric phase sorptive extraction such as extraction time, matrix pH, stirring speed, type and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Kaur et al in 2019 [51] developed and validated a rapid extraction and clean-up method using selective fabric phase sorptive extraction combined with gas chromatography and mass spectrometry for the determination of broad polarity spectrum emerging pollutants, ethyl paraben, butyl paraben, diethyl phthalate, dibutyl phthalate, lidocaine, prilocaine, triclosan, and bisphenol A in various aqueous samples. Some important parameters of fabric phase sorptive extraction such as extraction time, matrix pH, stirring speed, type, and volume of desorption solvent were investigated and optimized.…”
Section: Applicationsmentioning
confidence: 99%
“…Kaur et al in 2019 [51] developed and validated a rapid extraction and clean-up method using selective fabric phase sorptive extraction combined with gas chromatography and mass spectrometry for the determination of broad polarity spectrum emerging pollutants, ethyl paraben, butyl paraben, diethyl phthalate, dibutyl phthalate, lidocaine, prilocaine, triclosan, and bisphenol A in various aqueous samples. Some important parameters of fabric phase sorptive extraction such as extraction time, matrix pH, stirring speed, type, and volume of desorption solvent were investigated and optimized.…”
Section: Applicationsmentioning
confidence: 99%
“…Switchable hydrophobicity solvents were used as homogeneous liquid–liquid microextraction solvent for variety of CECs including N,N‐dimethylcyclohexylamine (DMCA), N,N‐diethylethanamine (TEA), and N,N‐benzyldimethylamine (DMBA), and absolute extraction recoveries were in the range of 51%–103% (Lasarte‐Aragones, Alvarez‐Lueje, Salazar, & Toledo‐Neira, 2019). Kaur et al (2019) developed a method using fabric phase sorptive extraction (FPSE) coupled with GC‐MS for the simultaneous determination of broad polarity spectrum CECs (including ethylparaben, butylparaben, diethyl phthalate, dibutyl phthalate, lidocaine, prilocaine, TCS, and BPA) in tap, ground, municipal, and wastewater samples. Based on the validation experiment and comparative results, they demonstrated that this measure was a rapid, reliable, and sensitive multi‐residue analytical method, since it took less time for sample preparation with satisfactory precision and recovery.…”
Section: Monitoringmentioning
confidence: 99%
“…In recent years, magnetic solid‐phase extraction (MSPE) technology shows a good application potential for the enrichment of trace analyte, due to its simple and fast operation, high processing efficiency, and wide range of applications [13,14]. MSPE adsorbents combine numerous advantages such as large surface area simple manipulation, high separation efficiency, high reusability, and environmental friendliness with magnetic microparticles placed in a solution or suspension containing analytes causing selective adsorption on solid surfaces [15–17]. Therefore, the synthesis of new adsorbents for MSPE is an urgent need.…”
Section: Introductionmentioning
confidence: 99%